2013
DOI: 10.1007/s10897-013-9573-7
|View full text |Cite
|
Sign up to set email alerts
|

Deaf Genetic Testing and Psychological Well‐Being in Deaf Adults

Abstract: Limited data suggest that enhanced self-knowledge from genetic information related to non-medical traits can have a positive impact on psychological well-being. Deaf individuals undertake genetic testing for deaf genes to increase self-knowledge. Because deafness is considered a non-medical trait by many individuals, we hypothesized that deaf individuals receiving a genetic explanation for why they are deaf will experience increased psychological well-being. We report results from a prospective, longitudinal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 57 publications
(82 reference statements)
0
23
0
Order By: Relevance
“…Benefits can include providing etiologic information, identifying (or allaying concerns about) comorbidities that may need referral for specialty care, planning for future medical and educational needs, facilitating estimations of the likelihood of recurrence, allowing families to better plan for the birth of a deaf or hard-of-hearing child, relieving the guilt that some parents may feel about having a child with hearing loss, enhancing ACMG PrACtiCe Guidelines psychological well-being, dispelling misinformation, and facilitating referral for unrelated hereditary conditions such as familial cancer. 48,[70][71][72][73][74][75][76][77][78][79] Furthermore, if mitochondrial DNA mutations associated with genetic susceptibility to aminoglycoside ototoxicity are discovered, it may be possible for relatives to avoid precipitating medications. [53][54][55] As with any genetics evaluation, clear communication between the genetics professionals and their patients is important for the provision of effective genetics services.…”
Section: The Importance Of Genetic Evaluation and Genetic Counseling mentioning
confidence: 99%
“…Benefits can include providing etiologic information, identifying (or allaying concerns about) comorbidities that may need referral for specialty care, planning for future medical and educational needs, facilitating estimations of the likelihood of recurrence, allowing families to better plan for the birth of a deaf or hard-of-hearing child, relieving the guilt that some parents may feel about having a child with hearing loss, enhancing ACMG PrACtiCe Guidelines psychological well-being, dispelling misinformation, and facilitating referral for unrelated hereditary conditions such as familial cancer. 48,[70][71][72][73][74][75][76][77][78][79] Furthermore, if mitochondrial DNA mutations associated with genetic susceptibility to aminoglycoside ototoxicity are discovered, it may be possible for relatives to avoid precipitating medications. [53][54][55] As with any genetics evaluation, clear communication between the genetics professionals and their patients is important for the provision of effective genetics services.…”
Section: The Importance Of Genetic Evaluation and Genetic Counseling mentioning
confidence: 99%
“…All these studies, however, have contradicted the studies done by [19] and [20]. Meanwhile, [21] found that genetic excuse (parents status of hearing) did have a significant association with the students' psychological well-being.…”
Section: Previous Studiesmentioning
confidence: 91%
“…For consistency, these variables are treated using the same categorizations described in other publications from this study [6], [36], [40]. Potential confounders such as enrollment site, genetic counselor, and interpreter were recorded for each participant.…”
Section: Methodsmentioning
confidence: 99%